EFFECT OF MULTI MICRONUTRIENT SUPPLEMENTATION ON HEMOGLOBIN LEVELS IN PREGNANT WOMEN WITH ANEMIA - Rati Purnama Sari; Noor Pramono; Sri Wahyuni; Muchlis Achsan Udji Sofro; Melyana Nurul Widyawati (Belitung Raya Foundation, Indonesia, 2017)
Background: The coverage of 90 Fe tablets in Semarang in 2015 was 26.619 of 29.490 pregnant women (97%) but the incidence of anemia in pregnant women was still quite high. One important factor which influences the levels of hemoglobin is multi micronutrient. Objective: This study aims to analyze the changes in hemoglobin levels with multi micronutrient supplementation in pregnant women with anemia. Methods: A quasi-experimental study with randomized control group pre-posttest design. The study samples were 40 pregnant women with gestational age of 20 ± 1 weeks divided into two groups, the intervention group (multi micronutrient supplementation) and the control group (Fe supplementation) for six weeks. The study was conducted from November 2016 to January 2017. The levels of hemoglobin were measured using cyanmethemoglobin. Paired t test and independent t test were used for data analyses. Results: The average of the increase in hemoglobin levels after multi micronutrient supplementation was 1.545 (1.292) g/dl, whereas the average of the increase in hemoglobin levels after Fe supplementation was 0.757 (0.742) g/dl. The difference in hemoglobin levels before and after multi micronutrient supplementation was significantly different (p=0.049). Cohen’s d effect size test showed value of 0.748. Conclusion: Multi micronutrient supplementation could improve hemoglobin levels. The increase in the levels of hemoglobin with multi micronutrient supplementation was higher than Fe supplementation.